Recent Advances in Green Solvents - Haghbakhsh, Reza; Raeissi, Sona; Craveiro, Rita (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Green chemistry", as a rather novel field of chemistry and chemical engineering, is one of the key routes to assist researchers in sustainable development. Among the most valuable assets of green chemistry, "green solvents" are primary candidates to replace the industry workhorses, i.e., conventional harmful solvents.